PANDANGAN DUNIA GHASSAN KANAFANI DALAM CERPEN “ARDHU AL-BURTUQOL AL-HAZIIN” - Saila Fadhila Ulfa (An-Nahdah Al-'Arabiyah, 2023)
This research aims to reveal the author's worldview, namely Ghassan Kanafani as a collective subject in his short story entitled "Ardhu al-Burtuqol al-Haziin" in an anthology of short stories with the same title using the genetic structuralism perspective of Lucian Goldmann. Goldmann's genetic structuralism emphasizes the analysis of the author's worldview as a representative of a particular social group, with his analysis departing from the structure of the literature work itself. Three research variables in genetic structuralism are the structure of literary works, worldview, and social structures. This research is qualitative-descriptive research with a dialectical method of analysis. The result of the discussion is there are many binary oppositions found in this short story “Ardhu al-Burtuqol al-Haziin”. Ghassan’s worldview in this short story is the economic downturn of the Palestinian people due to the 1948 Nakba Day and the loss of their national identity which was symbolized by an orange. This Ghassan Kanafani's worldview is the view of his group, namely the nationalist social group of workers and peasants.